INVESTIGATING EFL PRE-SERVICE TEACHERS' BELIEFS AND PRACTICES ON THE USE OF THE FIRST LANGUAGE (L1): A CASE STUDY IN ONE INDONESIAN UNIVERSITY - Glory Euodia, - (2022)
The use of the first language (L1) in EFL context has long been seen to be quite controversial. Some viewed the language only as a hindrance to the learning process while others have differing thoughts. Despite its rising popularity, only a handful of studies had their primary focus on what EFL pre-service teachers believed about the issue of L1 use in the classroom. Thus, the current study aimed at investigating what three EFL pre-service teachers, who were conducting their teaching practicum at the secondary level, believed about the use of L1 and how these beliefs are present in their teaching practice. At the time of the research, all three participants were a part of the English department of one Indonesian university in Bandung and were conducting their teaching practicums. A series of semi-structured interviews and classroom observations were done to collect the data, which were then analysed with thematic analysis. The findings showed that all participants viewed the L1 as a beneficial resource for the classroom, with two of them stating that it is crucial to use the L1 judiciously. The participants' teaching practices demonstrated that they were open to both their students' and their own uses of L1. However, the participants showed some struggle in maintaining a judicious use of L1 due to several reasons. This demonstrates a need for teacher education programs to prepare future teachers with the understanding of how to judiciously use the L1.